The Design of Web-Based Learning Using Google Sites for Teaching Heat and Temperature Topic - Raffa Fitra Ramadannisa; Mellyana Mega Hartina (Universitas Negeri Jakarta, 2021)
The limited variety of learning media will create various learning problems. One of the problems that arise is the lack of motivation to learn and low learning outcomes. These problems can be overcome by developing learning media integrated with technology such as web-based learning. This study aims to produce web-based learning using Google Sites on Heat and Temperature topics for high school students. The media development used the 4D model with the following stages: 1) Define, 2) Design, 3) Develop. The design and development stages of the media involve experts who assess two aspects, namely material and media design. The average result of media expert's validation is "very feasible". The average effect of material expert validation is "feasible." Based on the validation results by experts, this media is feasible to be used as a learning medium that helps students learn Heat and Temperature topics. The weakness in this research was that the learning design on the developed media was not very relevant to the learning objectives and basic competencies. Researchers hope to develop a learning media with learning designs that are more relevant to learning objectives and basic competencies in the future.